Two lives of a man : an autobiography - Gurdial Singh, 1933-; National Book Trust (New Delhi, India); Paramjit Singh (New Delhi : National Book Trust, 2010)
Autobiography of a Panjabi author
Keywords: Gurdial Singh ĉd 1933-; Authors, Panjabi -- 20th century -- Biography